Erratum: Effects of the Junior Master Gardener’s (JMG) Curriculum on Guatemalan Students’ Knowledge Gain and Attitude toward Science - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "Glenn, A., & Wingenbach, G. (2015). Effects of the Junior Master Gardener’s (JMG) Curriculum on Guatemalan Students’ Knowledge Gain and Attitude toward Science. Journal of International Agricultural and Extension Education, 22(2), 62-73” was incorrect as published. The correct DOI is: 10.4148/2831-5960.1260